The concept of security in Ancient Greece : an analysis through Ancient Greek intellectuals - Passakou, Pinelopy Nely (Array, 2020)
An early stage of a specific custom linked to the Ancient Olympic Games can be considered as one of the most powerful messages of the Greeks regarding their general views on security matters. For ancient Greeks, security was closely linked to war. Back then, the war went beyond protection from enemy invasion, something we would by definition call security nowadays. The article reviews the concept of security (“ἀσφάλεια,” asfalia) and its meaning as stability against and prevention of possible falls, and to be protected from danger.